Primary Pericardial Epithelioid Angiosarcoma: A Diagnostic Dilemma: A Case Report - Tahmineh Mollasharifi; Behrang Kazeminezhad (Iranian Society of Pathology, 2021)
The incidence of pericardial epithelioid angiosarcoma is rare. Angiosarcoma of pericardium may coat the pericardium in a diffuse fashion. Diagnosis of an angiosarcoma is challenging and may be easily mistaken as constrictive pericarditis. Herein, a case of primary pericardial angiosarcoma is reported in a 16-year-old female. Patient presented with chest pain and dyspnea on exertion, regarded as constrictive pericarditis. Pericardectomy was performed and histopathologic examination showed pleomorphic epithelioid cells exhibiting hyperchromatic nuclei, prominent nucleoli and eosinophilic cytoplasm arranged in sheets and occasionally lined irregular vascular spaces. Moreover, immunohistochemical staining revealed that tumor cells were positive for CD31 and vimentin. The patient received chemotherapy with adriamycin, ifosfamide, and mesna. Unfortunately, the patient died of cardiac involvement and pleural metastases less than three months following the operation. Primary pericardial angiosarcoma is rare and difficult to diagnose, especially epithelioid variant. Immunohistochemical assessment is required to confirm the final diagnosis.